64.6k views
3 votes
-4(2x - 4) = 2(2x - 1)​

User Seungwon
by
5.1k points

2 Answers

3 votes

Answer:

The answer is X = 0.67

User Dorin Niscu
by
5.5k points
5 votes

Answer:

-2x = -3 [Simplified Version] | X = 0.67

Explanation:

-4(2x - 4) = 2(2x - 1)

-8x + 16 = 4x - 2 [Distributive Property]

Subtract 16 on both sides

-8x = 4x - 18

Subtract 4x on both sides

-12x = -18

Divide by -12

X = 0.67

User ColinTea
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.